Religious Cooperation in Plural Ghana: Challenges and Ways for Improvement - Ernest Jnr Frimpong; Jonathan E. T. Kuwornu-Adjaottor; Makafui Margaret Tayviah; Michael Frimpong (E-Journal of Religious and Theological Studies, 2024)
There is a global call for religious cooperation and tolerance, and it is a non-negotiable necessity for Ghana, through a collective responsibility. This study thus investigated the perspectives of Ghanaians on the religious situation in Ghana. It looked at whether or not Ghana is a “one religion” State, by exploring the existence of several religions in Ghana. The global advocacy for religious cooperation motivated this study to explore some challenges hindering religious cooperation in Ghana, and ways for improvement. Using a mixed methodology of quantitative and qualitative designs, the study sampled 225 individuals ethically from the Faculty of Social Sciences in KNUST, Kumasi, Ghana. Primary data was obtained through questionnaires and interviews. The findings revealed that Christianity, Islam and African Traditional Religion are the three main religions amongst others in Ghana. A majority of 179 respondents indicated that Ghana has plural religions and is not a “one religion” State, hence, a non-negotiable advocacy for religious cooperation. The majority of these advocates are youth within the age brackets of 15-25 years, followed by adults within 36-45 years. Despite challenges hindering religious cooperation in Ghana such as religious, social, cultural and political barriers, the practice of respect, tolerance and value toward one another and interfaith relations, could guarantee some improvement. Therefore, whether Christians, Muslims, Traditionalists or the Other, one has to be and behave religiously inclusive, tolerant, and humble toward the other. Whether in speech or actions, one should give a listening ear to the other. This paper is relevant for peace and interfaith studies.